MORPHOMETRIC EVALUATION OF THE FORAMEN MAGNUM USING COMPUTED TOMOGRAPHIC IMAGES IN NEUROPSYCHIATRIC HOSPITAL MAIDUGURI, NORTHEASTERN NIGERIA - Zirahei JV; Amaza DS; Mailabari HY (Ntec Specialist, 2019)
The foramen magnum (FM) is an important landmark of the skull base. It is of particular interest in anthropology, anatomy, surgery and other medical fields because of its shape, relations and the structures it transmits. Knowledge of the anatomy of the FM and the structures around it is significant in sex determination and in surgical operations involving the basic ranium. The present study was aimed at the analysis of the antero-posterior diameter (APD), mid-transverse diameter (MTD), and the different shapes of the FM in the sample population. Method: The sample population for the present study which comprised of basicranial Computed Tomographic (CT) images of 110 patients (60 males and 50 females) with an average age of 18-65 years were obtained from the Federal Neuropsychiatric Hospital, Maiduguri, Borno State-Nigeria. Results: Males subjects showed higher mean value of APD (34.80 mm) compared to females (30.50 mm) and the differences observed was statistically significant at p less than 0.001. Similarly, males showed higher mean value of MTD of FM (31.60 mm) when compared to females (29.20 mm) and the differences observed was statistically significant at p less than 0.001. The study showed oval-shaped foramen magnum as most common (63% in males and 64% in females). The present study also observed the spherical and round shapes which constituted 22% and 25% in male and female respectively, in the sampled population. Pea-shaped and kite-shaped Foramen magnum was 3.3% occurrence in males and zero percent in females. Conclusion: The results of the present study revealed that, measurements of for amenmagnum is a valuable tool and is suitable for sex identification when other methods are not applicable